2016
DOI: 10.1093/gastro/gow032
|View full text |Cite
|
Sign up to set email alerts
|

Care of inflammatory bowel disease patients in remission

Abstract: Inflammatory bowel disease (IBD) comprises two distinct conditions: ulcerative colitis and Crohn’s disease, both of which are chronic, relapsing disorders carrying significant morbidity, mortality and healthcare costs. With growing attention to coordinated healthcare for patients with chronic systemic diseases, this review focuses on the care of IBD patients in remission, their concerns, quality of life, follow-up, the role of primary care physicians and the IBD-specific aspects of long-term care. We did an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 128 publications
(128 reference statements)
0
8
0
Order By: Relevance
“…Although IBD is marked by its chronic, unpredictable nature, patients can and do experience relief from active disease during periods of remission; during which research has shown differences in anxiety or depression rates. 13,14 Based upon the EST assertions stated above; remission would likely serve to moderate the relationship between IBD and PTSD symptomology as a time period with decreased physical symptoms and thus decreased perceptions of threat. In addition, patients' expectations of the longevity of their remission may similarly serve to decrease perceptions of threat.…”
Section: Illness-induced Ptsd and Enduring Somatic Threatmentioning
confidence: 99%
“…Although IBD is marked by its chronic, unpredictable nature, patients can and do experience relief from active disease during periods of remission; during which research has shown differences in anxiety or depression rates. 13,14 Based upon the EST assertions stated above; remission would likely serve to moderate the relationship between IBD and PTSD symptomology as a time period with decreased physical symptoms and thus decreased perceptions of threat. In addition, patients' expectations of the longevity of their remission may similarly serve to decrease perceptions of threat.…”
Section: Illness-induced Ptsd and Enduring Somatic Threatmentioning
confidence: 99%
“…Nutrient composition of daily diets including protein, fat, carbohydrate and dietary fibre have different effects on IBD management [41]. Therefore, nutrition interventions may play an important role in the improvement of IBD symptoms and in disease remission [42]. In the past few years, several dietary interventions have been studied for potential therapeutic effects on IBD [43].…”
Section: Introductionmentioning
confidence: 99%
“…This approach aims to support treatment, care and disease management, and reduce avoidable face-to-face consultations between doctor and patient [ 6 ]. Within IBD, patients daily life experience of the disease and changes herein associates with the state of disease and possibly need of action, thereby being a suitable condition for digital PRO assessment [ 7 , 8 ]. Use of digital PROs also has the potential to increase patient empowerment and improve healthcare [ 1 , 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%